EXPLORING ENGLISH TEACHERS’ PERCEPTION TOWARDS HIGHER ORDER THINKING SKILL (HOTS) IN THE 21ST CENTURY LEARNING (Proceedings of the International Conference on Future of Education, 2019)
Higher Order Thinking Skill (HOTS) is crucial in the 21st century learning process since it requires high ability to think critically and it requires teachers to have appropriate skill to face technological and global challenge, therefore, it is essential to study about Higher Order Thinking Skill (HOTS) and the relation with teachers’ perception. The study aimed to investigate teachers' perceptions towards Higher Order Thinking Skill (HOTS) and to know how it is reflected in teaching and learning process. This study used descriptive qualitative design. In obtaining the data about teachers' perceptions towards Higher Order Thinking Skill (HOTS), the researcher used a questionnaire and in-depth interview. The questionnaire was distributed to 10 teachers from different school and background knowledge in Java. The results showed that the teachers who were aware with the important of HOTS tend to foster their students in mastering HOTS and foster students to have high skill in problem solving and critical thinking, while the teachers who were lack of awareness will focus on giving their students with task relating with recalling ability only. Additionally, it was also found that teachers having positive perception towards HOTS taught their students using method that foster students to have high skill in problem solving and critical thinking.
Keywords: Teacher's Perception; Higher Order Thinking Skills (HOTS); 21st Century Learning